Frege's detour an essay on meaning, reference, and truth - Perry, John 1943- (Oxford University Press, 2019)
"John Perry offers a rethinking of Gottlob Frege's seminal contributions to philosophy of language. Frege's innovations provided the basis of modern logic, but his influence in other areas should not be understated. For instance, the view that he developed in "On Sense and Reference", the most studied essay in the philosophy of language, dominated twentieth-century work in the field and continues to be very influential. Perry explains and charts the development of Frege's views in this area, and argues that his doctrine of indirect reference directed philosophy of language on a long detour from which only now can we emerge. Perry advocates a move away from indirect reference and presents an alternative framework which does not require the abandoning of circumstances in the references of sentences."--
Keywords: Frege, Gottlob -- 1848-1925 -- Über Sinn und Bedeutung; Sprachphilosophie; Frege, Gottlob / 1848-1925; Frege, Gottlob / 1848-1925 / Über Sinn und Bedeutung; Reference (Linguistics); Meaning (Philosophy); Truth; Über Sinn und Bedeutung (Frege, Gottlob)